A new experimental approach to the pushover analysis of masonry buildings. (15th January 2015) - Foti, Dora
Abstract: The present paper proposes a new approach for the pushover analysis of masonry structures: the shear strength of a masonry building is determined using experimental values combined with an analogy with rock masses. The shear strength criterion of Mohr–Coulomb is used, the values for the cohesion and friction angle being obtained by the non-linear criterion of Hoek–Brown for rock masses. The results of the proposed method are in good agreement with the values of the shear strength obtained using the Italian Code (NTC 08) for an LC3 level of knowledge of a masonry structure.